Simple Method For Designing Inventory Management System - Lila Setiyani (Faktor Exacta, 2018)
The development of information technology encourages PT. Zalfa Mandiri to improve the effectiveness and efficiency of operational processes that occur. PT. Zalfa Mandiri as distribution a pharmaceutical company is aware that the conventional operational-based processes that occur at the moment have many obstacles that cause lost control of products that can affect stock taking and reporting processes. Based on these problems researchers want to provide solutions to PT. Zalfa Mandiri by designing a system that can help in managing pharmaceutical product inventory. In this system design process, researchers use a prototype method which is an approach in software engineering, so that in this study a system design can be produced that can be considered by PT. Zalfa Mandiri in managing pharmaceutical product inventory.Keywords: inventory , design system, prototyping, pharmaceutical .